2017
DOI: 10.1016/j.ijom.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional aesthetic assessment of class II patients before and after orthognathic surgery and its association with quantitative surgical changes

Abstract: The aim of this study was to compare evaluations of the aesthetic outcome of class II orthognathic patients, as performed by observers with varying expertise using three-dimensional (3D) facial images, and to examine the relationship of aesthetic ratings in relation to quantitative surgical changes. Pre- and postoperative 3D facial images of 20 surgically treated class II patients (13 female, 7 male) were assessed for aesthetics by orthodontists, maxillofacial surgeons, and laypeople. Attractiveness ratings fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…3 Even though quantitative studies exist in the literature, these devices have barely been compared in a qualitative manner. 24,27,28 Stebel et al qualitatively compared 2D and 3D stereophotogrammetry images to evaluate nasolabial aesthetics and found that SPG was more reliable and informative than 2D imaging, which corresponds with our findings. 28 However, in our study, the observers were more confident with LS than with 2D images, in contrast with the findings of Zogheib et al 24 The main limitations of this study are related to laser scanning, such as motion artefacts in the orbital region related to the blinking reflex, the application of chin support, and a long capture process, which might have influenced the results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…3 Even though quantitative studies exist in the literature, these devices have barely been compared in a qualitative manner. 24,27,28 Stebel et al qualitatively compared 2D and 3D stereophotogrammetry images to evaluate nasolabial aesthetics and found that SPG was more reliable and informative than 2D imaging, which corresponds with our findings. 28 However, in our study, the observers were more confident with LS than with 2D images, in contrast with the findings of Zogheib et al 24 The main limitations of this study are related to laser scanning, such as motion artefacts in the orbital region related to the blinking reflex, the application of chin support, and a long capture process, which might have influenced the results.…”
Section: Discussionsupporting
confidence: 88%
“…28 However, in our study, the observers were more confident with LS than with 2D images, in contrast with the findings of Zogheib et al 24 The main limitations of this study are related to laser scanning, such as motion artefacts in the orbital region related to the blinking reflex, the application of chin support, and a long capture process, which might have influenced the results. 1,27,29 To overcome these limitations, we recommend utilizing marker-free fixed 3D stereophotogrammetric systems such as the 3D Vectra ® H1, 3dMDface TM (3dMD LLC, Atlanta, USA) and Di3D TM (Dimensional Imaging, Glasgow, UK) imaging systems. 30 The reliability of the subjective observations might have been affected by the experience and relatively small number of the observers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus untreated, the patients would have suffered a steady decrease simply owing to ageing, and this effect is insufficiently accounted for when comparing to pre-treatment score. Second, it is a noted phenomenon seen in numerous investigations that the use of a discrete scale to score intra-individual changes of facial aesthetics in orthognathic patients ordinarily results in small quantitative increments 9,16,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been devoted to accurately evaluate the aesthetic outcome of orthognathic treatment. Improvements in facial appearance have been studied based on self-reported scores of patients [6][7][8] or orthodontists and maxillofacial surgeons appraising the changes in soft tissue proportions and facial aesthetics 9 . However, all historical approaches fall short to adequately address the assessment of social attractiveness 10 .…”
mentioning
confidence: 99%
“…Facial symmetry perception may vary from observer to observer (Scheib et al, 1999). Also different parts of the face contribute differently to the perception of symmetry (Hwang et al, 2012; Storms et al, 2017).…”
Section: Symmetry Registrationmentioning
confidence: 99%